Grassland management, forage production and plant biodiversity in a Mediterranean grazing system - Salis L.; Marrosu M.; Bagella S.; Sitzia M.; Roggero P.P. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Mediterranean grazing systems have strongly affected the vegetation dynamics and grassland flora's composition at landscape scale. The aim of this study was to evaluate the impact of different management systems on forage production and plant biodiversity of grasslands in agro-pastoral farms of the dehesa landscape of North-eastern Sardinia. Sampling areas were located in grasslands characterized by different grazing system typologies (cattle and sheep), and by different type of soil management (short, medium and long rotation with forage crops). The effects of grazing animal species and type of agronomic management were evaluated. Agronomical and floristic data collected throughout the year allowed to assess herbage mass and herbage on offer seasonal dynamics, botanical composition and biodiversity indicators (Species Richness and Shannon's Index). In late spring, herbage mass and herbage on offer showed differences between types of grassland management. Grazing system typologies significantly influenced floristic composition but not the plant biodiversity indices.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)